(untitled) (Al-Jabal Journal of Humanities and Applied Sciences, 2025)
Abstract: The research aimed to evaluate the quality of groundwater and springs water in the city of Nalut using the Canadian Water Quality Index (CWQI). Samples were collected from four well sites and four of the springs targeted by the study during October 2023, Some of the natural and chemical properties of these samples were measured, namely: pH, solid dissolved materials, electrical conductivity, total hardness, calcium and magnesium ions, chloride, bicarbonate, sulfate, potassium, sodium, nitrate, phosphate, iron, and the results were compared with World Health Organization specifications 2011. Calculations were also performed for the (CWQI). The results concluded that the concentration of salts in the wells studied was high, which affected the water quality to the point that it ranged from poor to unfit for drinking.